2020
DOI: 10.15386/mpr-1372
|View full text |Cite
|
Sign up to set email alerts
|

Association between obesity and venous thromboembolism

Abstract: Background and aims. Obesity is associated with numerous pathological conditions, including venous thromboembolism (VTE). VTE is a multifactorial disease; more than half of the hospitalized patients are at risk for VTE. We aimed to assess the risk of VTE associated with obesity, taking into account the class of obesity (according to the body mass index), gender, age and the intervention of other acquired risk factors. Method. A case-control study including 732 patients was designed. Collected data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 31 publications
5
52
1
Order By: Relevance
“…For all we know, age has been identified as a VTE risk factor mainly due to the increased blood coagulability and prevalence of other predisposing factors such as immobilization and hospitalization. 28 , 30 , 31 In this study, an older age was weakly associated with a higher DVT risk, which suggested that age was still an unignorable factor in DVT prevention. D-dimer is widely used in clinical practice as an indicator to monitor DVT with a high sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…For all we know, age has been identified as a VTE risk factor mainly due to the increased blood coagulability and prevalence of other predisposing factors such as immobilization and hospitalization. 28 , 30 , 31 In this study, an older age was weakly associated with a higher DVT risk, which suggested that age was still an unignorable factor in DVT prevention. D-dimer is widely used in clinical practice as an indicator to monitor DVT with a high sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 54%
“… 23 Summarily, these existing research results ulteriorly illustrated that the low-grade inflammatory and impaired fibrinolysis state mediated by obesity itself was very likely to be a major reason for the increased risk of VTE. 25 , 28 , 29 Importantly, recent researches demonstrated that the abnormal expression of adipokines and microRNAs and the endothelial damage resulting from systemic oxidative stress could contribute to the pro inflammatory and prothrombotic effects exacerbated by excess body weight. 25 , 28 , 29 Although the specific association of a high BMI and VTE is still not clear, for the obese patients with PCL injury, there is quite a necessity to take some measures exactly as strengthening physical prevention, taking lipid-lowering medication, and anticoagulant intervention for a decrease in DVT incidence after knee arthroscopic PCL reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is a risk factor for thrombotic disorders, including venous thromboembolism (VTE), due to disruption of the balance between prothrombotic and antithrombotic adipokines, which leads to chronic inflammation, impaired fibrinolysis, and enhanced platelet activation inducing the coagulation cascade [2,3]. Studies have reported up to a 6.2-fold increase in the risk of VTE due to obesity [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Among patients with obesity, defined as a body mass index (BMI) >30 kg/m 2 , there is a 6.2-fold increased risk for VTE. 3 This risk has been shown to have a direct correlation with an increasing BMI, placing patients with severe obesity, defined as a BMI >40 kg/m 2 , at even higher risk of VTE occurrence. 3 Direct oral anticoagulants (DOACs) are the standard of care for VTE treatment.…”
Section: Backg Rou N Dmentioning
confidence: 99%